Carrier Screening for Single-Gene Disorders – A Brief Review - Katya Kovacheva; Slavena Nikolova; Zornitsa Kamburova (Journal of Biomedical & Clinical Research, 2021)
Carrier screening (CS) is an approach to pre-reproductive identification of couples at risk of having offspring with a single-gene disorder (SGD). The goal of CS is to facilitate reproductive autonomy and informed decision-making of the revealed risk couples. Initially, CS was introduced in the 1970s among the Ashkenazi Jewish population in the USA with a high incidence of Tay-Sachs disease. Until recently, CS had a limited application, mainly among individuals of a particular ethnicity or family history of SGD, and a limited number of conditions are included. Implementing the revolutionary technology of next-generation sequencing revealed a much more comprehensive range of possibilities for CS. The expanded alternative variant introduced a new concept that allows screening for hundreds to thousands of SGDs without pre-selection of individuals based on their ancestry or family history. Furthermore, the number of detected pathogenic variants is much higher compared to the traditional CS. Currently, there is insufficient experience with the application of expanded CS, and the lack of uniform guidelines is a major problem when it comes to massive implementation. Nevertheless, the significant potential of the expanded CS has given rise to a growing interest in it and provoked in-depth discussions about the opportunities of widespread application in practice.